Update on the Renal Effects of Anticancer Agents. Issue 3 (November 2017) - Perazella, Mark A.
Anticancer drug nephrotoxicity is a common problem encountered by the nephrologist. The number of drugs causing acute and chronic kidney injury as well as electrolyte and acid-base disturbances has increased significantly over the past 10 to 20 years. Clinicians must be knowledgeable in the renal metabolism and excretion of these agents to assure efficacy and to avoid systemic toxicity, especially in patients with underlying kidney disease. Chemotherapeutic drugs induce acute kidney injury from a number of lesions including acute tubular injury, acute interstitial nephritis, and a variety of glomerular injuries. In addition to nephrotoxicity associated with conventional chemotherapy, the emergence of targeted therapies and novel immunotherapies has increased the occurrence of drug-induced acute and chronic kidney injury in cancer patients. This article will reflect some of the information on anticancer drug nephrotoxicity, which I presented at the New Horizons in Nephrology Updates in Onco-Nephrology Symposium in Philadelphia, Pennsylvania, USA.